Strategic Conflicts on the Horizon: R&D Incentives for Environmental Technologies - Daniel Heyen (University of Heidelberg, Department of Economics, 2015)
Technological innovation is a key strategy for tackling environmental problems. The required R&D expenditures however are substantial and fall on self-interested countries. Thus, the prospects of successful innovation critically depend on innovation incentives. This paper focuses on a specific mechanism for strategic distortions in this R&D game. In this mechanism, the outlook of future conflicts surrounding technology deployment directly impacts on the willingness to undertake R&D. Apart from free-riding, a different deployment conflict with distortive effects on innovation may occur: Low deployment costs and heterogeneous preferences might give rise to 'free-driving'. In this recently considered possibility (Weitzman 2012), the country with the highest preference for technology deployment, the free-driver, may dominate the deployment outcome to the detriment of others. The present paper develops a simple two stage model for analyzing how technology deployment conflicts, free-riding and free-driving, shape R&D incentives of two asymmetric countries. The framework gives rise to rich findings, underpinning the narrative that future deployment conflicts pull forward to the R&D stage. While the outlook of free-riding unambiguously weakens innovation incentives, the findings for free-driving are more complex, including the possibility of super-optimal R&D and incentives for counter-R&D.
urn:nbn:de:bsz:16-heidok-183337
Keywords: 330